ANALYTICAL DESIGN METHOD OF 3 KW, 200 RPM PERMANENT MAGNET GENERATOR FOR RENEWABLE ENERGY POWER PLANT APPLICATIONS - Irasari, Pudji; Alam, Hilman Syaeful; Kasim, Muhammad (Ketenagalistrikan dan Energi Terbarukan, 2013)
This paper discusses the analytical design method of 3 kW, 200 rpm radial flux permanent magnet generator (PMG) for renewable energy power plant applications. The proposed design method is conducted in two stages, i.e. initiation and validation stages. In the initiation stage, some of the parameters should be specified with values, such as output power, specific magnetic loading, rotation, etc. Results of this stage are detail dimensions of the stator and rotor, which then serve as a reference to recalculate the flux density (entering validation phase). With the new value of specific magnetic loading, all related parameters should also be recalculated, such as the number and diameter of the turns. Furthermore, design is validated by testing the prototype of generator using water resistance load. The test results show that it produces 3043.64 W of power and 253.51 V of voltage at 200 rpm. Compared to the analytical calculation, the power is 0.86% lower and the voltage is 12.45% higher. These results illustrate that the design has been performed properly since the targeted output power can be achieved at the desired speed. Paper ini membahas metoda perancangan analitik generator magnet permanent fluks radial 3 kW, 200 rpm untuk aplikasi pembangkit listrik energi terbarukan. Metoda perancangan yang diusulkan dilakukan dalam dua tahap, yaitu tahap inisiasi dan tahap validasi. Dalam tahap inisiasi, beberapa parameter nilainya harus ditentukan, seperti daya keluaran, specific magnetic loading, putaran, dll. Hasil akhir tahap ini berupa dimensi detil stator dan rotor yang kemudian dijadikan sebagai acuan untuk menghitung kembali specific magnetic loading (memasuki tahap validasi). Dengan nilai specific magnetic loading yang baru, parameter lain yang terkait harus dihitung kembali, seperti jumlah dan diameter lilitan. Selanjutnya, desain divalidasi dengan menguji prototipe generator menggunakan beban tahanan air. Hasil pengujian menunjukkan bahwa generator membangkitkan daya 3043.64 W dan tegangan 253.51 V pada 200 rpm. Jika dibandingan dengan hasil perhitungan, daya eksperimen lebih kecil 0.86% sedangkan tegangannya, lebih besar 12.45%. Hasil tersebut menunjukkan bahwa metoda desain yang diusulkan telah dilakukan dengan teliti karena target daya keluaran dapat dicapai pada putaran yang diinginkan.